Recent progress of nanomedicine in the treatment of Alzheimer’s disease - Hu, Liqiang; Tao, Yiran; Jiang, Yanjiao; Qin, Feng (Frontiers in Cell and Developmental Biology, 2023)
Alzheimer's disease (AD) is the most common cause of memory disruption in elderly subjects, with the prevalence continuing to rise mainly because of the aging world population. Unfortunately, no efficient therapy is currently available for the AD treatment, due to low drug potency and several challenges to delivery, including low bioavailability and the impediments of the blood-brain barrier. Recently, nanomedicine has gained considerable attention among researchers all over the world and shown promising developments in AD treatment. A wide range of nano-carriers, such as polymer nanoparticles, liposomes, solid lipid nanoparticles, dendritic nanoparticles, biomimetic nanoparticles, magnetic nanoparticles etc., have been adapted to develop successful new treatment strategies. This review comprehensively summarizes the recent advances of different nanomedicine for their efficacy in pre-clinical studies. Finally, some insights and future research directions are proposed. This review can provide useful information to guide the future design and evaluation of nanomedicine in AD treatment.